Factors Affecting Level of Participation in the Management of Mangroves as Ecotourism Attraction: Lesson Learned from Cengkrong Watulimo, Trenggalek - Muhammad Izzuddin Faizal; Luchman Hakim; Nuddin Harahap (Journal of Indonesian Tourism and Development Studies, 2017)
Ecotourism development can not be separated from the social aspects of the people living around the tourist sites. One indicator that a tourist location is said to be ecotourism-based is the participation of community in the activities of management. This study aims to determine the effect of variables that exist on the level of community participation in the management of mangrove areas Cengkrong using Partial Least Square (PLS) method. The variables used in this study are: community characteristics, perceptions, norms, patterns of social relationships, and trust. From the research, the variables that have a dominant influence on the level of participation in the management of mangrove Cengkrong is variable of perceptions, norms, and trusts with the value of the effect size, respectively for 0.098, 0.204, and 0.431. While variable of trust has most influence to the coefficient path of community participation with a value of 0.64.Keywords: Ecotourism, Factors of Participation, Level of Participation, Partial Least Square (PLS).